2002
DOI: 10.1200/jco.2002.06.020
|View full text |Cite
|
Sign up to set email alerts
|

American Society of Clinical Oncology Technology Assessment on the Use of Aromatase Inhibitors as Adjuvant Therapy for Women With Hormone Receptor–Positive Breast Cancer: Status Report 2002

Abstract: The conclusions of the panel were endorsed by the ASCO Health Services Research Committee and the ASCO Board of Directors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(109 citation statements)
references
References 36 publications
4
98
0
7
Order By: Relevance
“…16 Tumor proliferation in human mammary carcinoma was also significantly altered by androgens. 13 The results of adjuvant treatment of breast cancer with aromatase inhibitors, which block the conversion of adrenal steroids (mainly androgens) into estrogens, have been reported 17 and underscore the important role of androgens in the stimulation of human mammary carcinoma growth. Furthermore, studies on the effects of androgens and antiandrogens on breast carcinomas in long-term tissue cultures indicated that some human breast carcinomas, at least in vitro, Androgen receptors and mammary and extramammary Paget's disease B Liegl et al may be stimulated by androgens.…”
Section: Discussionmentioning
confidence: 99%
“…16 Tumor proliferation in human mammary carcinoma was also significantly altered by androgens. 13 The results of adjuvant treatment of breast cancer with aromatase inhibitors, which block the conversion of adrenal steroids (mainly androgens) into estrogens, have been reported 17 and underscore the important role of androgens in the stimulation of human mammary carcinoma growth. Furthermore, studies on the effects of androgens and antiandrogens on breast carcinomas in long-term tissue cultures indicated that some human breast carcinomas, at least in vitro, Androgen receptors and mammary and extramammary Paget's disease B Liegl et al may be stimulated by androgens.…”
Section: Discussionmentioning
confidence: 99%
“…Endocrine therapies are the most effective systemic treatment of estrogen receptor a (ERa)-positive breast cancer, and over two-thirds of patients are considered to present with this kind of disease (EBCTCG, 1998;Chlebowski et al, 2002;Winer et al, 2002). Two major strategies mediate the efficacy of these therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Patient accrual was substantially limited by the introduction of aromatase inhibitors (12), which are now routinely used in patients discontinuing tamoxifen therapy at our medical center.…”
Section: Resultsmentioning
confidence: 99%